Correction of cosine oscillation to the improved correlation method of estimating the amplitude of gravitational background signal *Project supported by the National Natural Science Foundation of China (Grant Nos. 11575160, 11175160, 11275075, and 11511130011). (April 2017) - Wu 巫, Wei-Huang 伟皇; Tian 田, Yuan 苑; Xue 薛, Chao 超; Luo 罗, Jie 杰; Shao 邵, Cheng-Gang 成刚
Abstract : In the measurement of G with the angular acceleration method, the improved correlation method developed by Wu et al . (Wu W H, Tian Y, Luo J, Shao C G, Xu J H and Wang D H 2016 Rev. Sci. Instrum. 87 094501) is used to accurately estimate the amplitudes of the prominent harmonic components of the gravitational background signal with time-varying frequency. Except the quadratic slow drift, the angular frequency of the gravitational background signal also includes a cosine oscillation coming from the useful angular acceleration signal, which leads to a deviation from the estimated amplitude. We calculate the correction of the cosine oscillation to the amplitude estimation. The result shows that the corrections of the cosine oscillation to the amplitudes of the fundamental frequency and second harmonic components obtained by the improved correlation method are within respective errors.